Spatial images and activity areas in an urban environment : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Geography at Massey University - Hill, Peter (Massey University, 1981)
Cognitive-behavioural concepts and their introduction into geography are considered. A proposed schema suggests, and Research Hypotheses propose that the spatial schemata and activity area of individuals are interrelated and that constraints act upon this complex. Data are obtained, by means of a questionnaire/interview, for a population of 50 and evaluation of operational hypotheses is made with respect to this population. Analysis of the data provides strong support for the interactive association of direct experience in and cognition of an urban environment. For the individual, physical distance appears to be a poor proxy for cognitive distance, though a 'group image' is suggested. Temporal constraints are seen to operate as are social constraints on the immediate neighbourhood scale. Socio-economic and personal constraints are not in evidence, which further supports the role of direct experience in the development of spatial schemata. The need to differentiate between the nature and function of the spatial schemata and image is clearly shown.
Keywords: Geography; Environmental psychology; Geographical perception; Cities towns; Effect of environment on human beings